Temporal Trends in Chorioamnionitis by Maternal Race/Ethnicity and Gestational Age (1995–2010) - Fassett, Michael J. (Int J Reprod Med, 2013)
Objective. To characterize trends in chorioamnionitis (CAM) by maternal race/ethnicity and gestational age. Study Design. We examined trends in CAM from 1995–2010 among singleton births in all Kaiser Permanente Southern California hospitals (n = 471,821). Data were extracted from Perinatal Service System and clinical utilization records. Gestational age- and race/ethnicity-specific biannual diagnosis rates were estimated using the Poisson regression after adjusting for potential confounding factors. Results. Overall diagnosis rates of CAM increased from 2.7% in 1995-1996 to 6.0% in 2009-2010 with a relative increase of 126% (95% confidence intervals [CI] 113%–149%). From 1995-1996 to 2009-2010, CAM increased among the Whites (1.8% to 4.3%, P-value for trend <.001), Blacks (2.2% to 3.7%, P-value for trend <.001), Hispanics (2.4% to 5.8%, P-value for trend <.001), and Asian/Pacific Islanders (3.6% to 9.0%, P-value for trend <.001). The adjusted relative percentage change in CAM from 1995-1996 to 2009-2010 was for Whites [preterm 21% (9%–78%), term 138% (108%–173%)], for Blacks [preterm 24% (−9%–81%), term 62% (30%–101%)], for Hispanics [preterm 31% (3%–66%), term 135% (114%–159%)], and for Asian/Pacific Islanders [preterm 44% (9%–127%), term 145% (109%–188%)]. Conclusion. The findings suggest that CAM diagnosis rate has increased for all race/ethnic groups. This increase is primarily due to increased diagnosis at term gestation.